UniPR129 is a competitive small molecule Eph‐ephrin antagonist blocking in vitro angiogenesis at low micromolar concentrations. (28th August 2014) - Hassan‐Mohamed, I; Giorgio, C; Incerti, M; Russo, S; Pala, D; Pasquale, E B; Zanotti, I; Vicini, P; Barocelli, E; Rivara, S; Mor, M; Lodola, A; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The Eph receptor tyrosine kinases and their ephrin ligands are key players in tumorigenesis and many reports have correlated changes in their expression with a poor clinical prognosis in many solid tumours. Agents targeting the Eph‐ephrin system might emerge as new tools useful for the inhibition of different components of cancer progression. Even if different classes of small molecules targeting Eph‐ephrin interactions have been reported, their use is hampered by poor chemical stability and low potency. Stable and potent ligands are crucial to achieve robust pharmacological performance. Experimental Approach UniPR129 (the L‐homo‐Trp conjugate of lithocholic acid) was designed by means of computational methods, synthetized and tested for its ability to inhibit the interaction between the EphA2 receptor and the ephrin‐A1 ligand in an elisa binding study. The ability of UniPR129 to disrupt EphA2‐ephrin‐A1 interaction was functionally evaluated in a prostate adenocarcinoma cell line and its anti‐angiogenic effect was tested in vitro using cultures of HUVECs. Key Results UniPR129 disrupted EphA2‐ephrin‐A1 interaction with Ki = 370 nM in an elisa binding assay and with low micromolar potency in cellular functional assays, including inhibition of EphA2 activation, inhibition of PC3 cell rounding and disruption of in vitro angiogenesis, without cytotoxic effects. Conclusions and Implications The discovery of UniPR129 represents not only a major advance in potency compared with the existing Eph‐ephrin antagonists but also an improvement in terms of cytotoxicity, making this molecule a useful pharmacological tool and a promising lead compound.